Two carrier localizations in GaN/AlGaN multiquantum wells investigated by temperature dependent photoluminescence. Issue 5 (22nd December 2015) - Wu, Feng; Li, Yang; Tian, Wu; Zhang, Jun; Wang, Shuai; Dai, Jiangnan; Feng, Zhe Chuan; Chen, Changqing
Abstract: Carrier localization effect has been observed in GaN/AlGaN multiquantum wells (MQWs) by analyzing the temperature dependent photoluminescence (PL) results. Specifically, two neighbouring peaks can be seen in the PL spectra with an abnormal variation when increasing the temperature. A conduction band model with two minimal potentials corresponding to two carrier localizations is proposed to explain the PL spectra. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)